Algebra 2 Common Core

Published by Prentice Hall
ISBN 10: 0133186024
ISBN 13: 978-0-13318-602-4

Chapter 3 - Linear Systems - Get Ready!: 4

Answer

15

Work Step by Step

We simplify the expression first, then substitute the values in. We have $12(\frac{3}{4}x-\frac{1}{2}y)-6(\frac{1}{2}x-\frac{3}{4}y)=9x-6y-3x+\frac{9}{2}y=6x-\frac{3}{2}y=6(2)-\frac{3}{2}(-2)=12+3=15$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.